STRATEGI BERTAHAN HIDUP PEDAGANG KAKI LIMA DI SEKITAR MALL KOTA PEKANBARU - Ningsih, Auliya Dira; Marnelly, T. Romi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
At this time, street vendors are a phenomenon in urban areas, often found in public facilities or in crowds, one of which is on the side of the road around the Mall. This research was conducted in the city of Pekanbaru. The purpose of this research is to find out how the survival strategies of street vendors selling around the Pekanbaru city mall, knowing what obstacles are faced by street vendors around Pekanbaru city mall. In this study, the technique of taking the subject used purposive sampling which had already determined the criteria in this study. The theory used in this research is Edi Suharto's survival strategy. The results of this study are the obstacles faced by traders, namely the weather and unofficial trading places. PKL has three strategies for survival, namely an active strategy by empowering all existing potential, asking for help from family members and increasing working hours by having a side job to maintain the family economy even in a situation of shortage. The second strategy is passive, making savings by minimizing household expenses such as bringing supplies from home in trading activities and managing finances by saving money, the third network strategy, taking advantage of relationships that have been built in the social environment by borrowing money from official institutions such as pawnshops and cooperatives. Keywords: Mall, street vendors, survival strategies.